√338•(√392-√288+√522-√50)+3√242•2√2=
=√2·√13² × ( √2³·√7² - 12√2 + 3√58 - 5√2) + 3×11√2 ×2√2=
=13√2 × ( 14√2 -12√2 -5√2 + 3√58) + 33×2×2=
=13√2 × ( 3√58 - 3√2) + 132=
=13√116 - 39√4 + 132=
=13×2√29 - 39×2 + 132=
=26√29 - 78 + 132=
=26√2 + 54=
1536-(√2646-√384+3•√343•(√1008-√567)=
=1 536 - ( 21√6 - 8√6) + 3×7√7 ×( 12√7 - 9√7)=
=1 536 + 13√6 + 21×12×7 - 21×9×7=
=1 536 + 13√6 + 1 764 - 1 323=
=13√6 - 1 977
√288•(√192+√243-√675-√12)-√240=
=√2⁵·√3² × ( √8²·√3 + √3³ - √5²·√3³ - 2√3) - √2⁴·3·5=
=4×3√2 × ( 8√3 + 3√3 - 5×3√3 - 2√3) - 4√15=
=12√2 × ( 11√3 - 15√3 - 2√3) - 4√15=
=12√2 × ( - 6√3) - 4√15=
= - 72√6 - 4 √15=
= - 4 ×( 18√6 + √15)